Modulations of Nature in Latin American Literature: From Modernism to Contemporary Science Fiction - Roberto Chuit Roganovich (Estudios de Teoría Literaria)
In the 21st century, the two standardized representations of Nature that Latin American literature has accustomed us to have been disrupted. We no longer encounter the semantic axes of "abundance" or "scarcity," nor any of the possible nuances within the spectrum of this dichotomy, but rather a new one: an "other" Nature, marked by its "non-existence" or by its indistinguishable symbiosis with Culture. The present work attempts, therefore, to account for these mutations in order to contribute to the development of a new historiography of Latin American literature from the conceptual pivot of Nature.